FinFET Towards Nano-Transistor: A Review - Yasir Naif (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
This paper review the FinFET structure as a future transistor for analog and digital electronic circuits, and present its electrical characteristics depending on the important parameters for evaluating the MOSFETs structures like DIBL and Ion/Ioff.